HVDC LCC technology and power quality issues in cross-border electrical power transmission Russia - Finland; Innovative Smart Grid Technologies Conference Europe (ISGT Europe), IEEE PES - Zmaznov E. Yu. Evgeny Yurjevich; Lozinova N. G.; Suslova O. V.; Andreev M. V. Mikhail Vladimirovich; Ufa R. A. Ruslan Alexandrovich; Ruban N. Yu. Nikolay Yurievich; Suvorov A. A. Aleksey Aleksandrovich (2018, 2018)
Title screen